Influence of Intradialytic Aerobic Training in Cerebral Blood Flow and Cognitive Function in Patients with Chronic Kidney Disease: A Pilot Randomized Controlled Trial - Stringuetta Belik, Fernanda [UNESP]; Oliveirae Silva, Viviana Rugolo [UNESP]; Braga, Gabriel Pereira [UNESP]; Bazan, Rodrigo [UNESP]; Perez Vogt, Barbara [UNESP]; Costa Teixeira Caramori, Jacqueline [UNESP]; Barretti, Pasqual [UNESP]; De Souza Gonçalves, Renato [UNESP]; Fortes Villas Bôas, Paulo José [UNESP]; Hueb, João Carlos [UNESP]; Martin, Luis Cuadrado [UNESP]; Da Silva Franco, Roberto Jorge [UNESP] (Karger Publishers, 2018)
Background and Objectives: Changes in cerebral blood flow may play an important role in cognitive impairment among hemodialysis (HD) patients. Physical activity has a promising role in delaying cognitive impairment in general population, but there are only a few studies in HD to confirm this finding. We aimed to evaluate the effects of intradialytic aerobic training on cerebral blood flow and cognitive impairment in HD. Design, Setting, Participants, and Measurements: This is a pilot, controlled, randomized trial. Fifteen patients underwent intradialytic aerobic training 3 times a week for 4 months. The control group was comprised of another 15 patients. Results: Trained patients had a statistically significant improvement of cognitive impairment and basilar maximum blood flow velocity. The proportion of arteries with increased flow velocity was statistically significant between groups. Conclusions: Intradialytic aerobic training improves cognitive impairment and cerebral blood flow of patients in HD, suggesting a possible mechanism improving cognitive impairment by physical training in HD. These data still need to be confirmed by major trials.
Keywords: Cerebral arteries; Chronic kidney disease; Cognition; Hemodialysis; Physical activity